Pengaruh Variasi Dosis Pembersih Lantai Merek "W" terhadap Angka Kuman Lantai di Bangsal Dahlia RSUD Kota Yogyakarta - Antonius Riski Bayu Permana; Yamtana Yamtana; Heru Subaris Kasjono (Sanitasi: Jurnal Kesehatan Lingkungan, 2010)
The floor microbe number at nursing care of Yogyakarta public hospital at 18th of August 2008 did not fulfill the maximum thresholds permitted by the regulation This condition may lead to the incidence of nosocomial infection, so that proper disinfection should be taken into account. The study was aimed to know the most effective dose of cleaning liquid brand “W" using in declining the microbe number. The study was an experiment with pre-test post-test group design. The variation doses observed were 70 ml, 80 ml, and 90 ml which were dissolved into 1 liter water and to be used for 40 m² room width; and were conducted at Dahlia Ward. The floor cleaning process, the sampling and specimen taking process, as well as the microbe examination at microbiology laboratory followed the standard procedures. The data were analysed by using one way anova test and LSD test, and produce results that the declining difference of the microbe number among the three doses was statistically significant; and the most effec- tive dose was 90 ml cleaning liquid which on average could reduce 92,81% of the bacteria. Based on the results, it is advised for the hospital to use this dose for floor cleaning process.